Association of polymorphism in the transforming growth factor β1 gene with disease outcome and mortality in rheumatoid arthritis. Issue 8 (4th February 2005) - Mattey, D L; Nixon, N; Dawes, P T; Kerr, J
Abstract : Objective: To investigate whether polymorphism in the transforming growth factor β1 (TGFβ1) gene is associated with disease outcome in rheumatoid arthritis. Methods: 208 patients with established rheumatoid arthritis were genotyped for the TGFβ1 T869C polymorphism using an amplification refractory mutation system–polymerase chain reaction (ARMS-PCR) method. Disease severity was assessed by measuring radiographic damage by Larsen score and functional outcome by the health assessment questionnaire (HAQ). Patients were tracked on the NHS central register for notification of death, and the relation between TGFβ1 polymorphism and mortality was analysed using Cox proportional hazards regression. Results: Patients carrying a TGFβ1 T allele had a higher mean HAQ score than those without this allele (1.60 v 1.22, p = 0.04). The T allele was also associated with higher five year mean area under the curve (MAUC) erythrocyte sedimentation rate (ESR), and nodular disease. Larsen score was higher in patients with the TT genotype compared with CC + CT genotypes, although this was not significant after correction for disease duration. There was a trend of increasing mortality risk with T allele dose after adjustment for age, sex, and disease duration (hazard ratio = 1.6 (95% confidence interval, 1.1 to 2.4), p = 0.01). Conclusions: TGFβ1 T869C gene polymorphism is associated with disease outcome in rheumatoid arthritis. Carriage of the T allele (putatively associated with decreased TGFβ1 production) was associated with increased inflammatory activity and poor functional outcome, while increasing T allele dose was associated with worse survival.